Pengaruh Pengangguran dan Pertumbuhan Penduduk Terhadap Kemiskinan di Indonesia: Analisis Data Panel Tahun 2020-2024 - Farahdiba Farahdiba; M Rasyidin; M Saleh (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2026)
This study aims to analyze the effect of unemployment and population growth on poverty levels in Indonesia. The research was conducted across 34 provinces during the 2020–2024 period using secondary data obtained from the Central Bureau of Statistics. The study employed a quantitative approach with panel data regression analysis. The best model selection was carried out using the Chow, Hausman, and Lagrange Multiplier tests, which indicated that the Random Effect Model was the most appropriate. The results show that unemployment has a negative but statistically insignificant effect on poverty levels. This finding suggests that an increase in unemployment does not necessarily lead to higher poverty rates, possibly due to the role of the informal sector and social protection programs that help maintain household purchasing power. In contrast, population growth has a positive and significant effect on poverty levels. Simultaneous testing shows that both variables jointly have a significant effect on poverty, with a coefficient of determination (R²) of 3.86 percent, indicating a relatively low contribution to variations in poverty. These results imply that other factors beyond the research variables, such as income inequality, education quality, and access to basic services, have a more dominant influence. The study emphasizes the importance of integrated policies focused on controlling population growth and improving job quality to sustainably reduce poverty rates.